BUILSA COMMUNITY VULNERABILITY AND CAPACITY ASSESSMENT IN THE UPPER EAST REGION OF GHANA - Simon, Kanlisi Kaba; Aasoglenang, Arkum Thaddeus (European Scientific Journal, ESJ, 2013)
Research into disaster management through out the world has not been able to catch up with the frequency and scale of disaster events. Even though the developed countries have made tremendous advances in the improvement of disaster management, the same cannot be said of the underdeveloped world and Ghana particularly the Builsa District. Most of the time, when disasters occur, victims try to manage them from within their communities based on existing capacities while efforts are made to seek external assistance. The Builsa Community Vulnerabilities and Capacity Assessment (VCAs) therefore aimed at co-documentation and re-invigoration of community knowledge and experiences in disaster management and building the capacity of communities to address the most urgent situations of vulnerability. VCAs were held in five communities that were most affected by the 2007 drought and floods. The exercise involved community analysis of their disaster hazard experiences, disaster trends, traditional coping strategies and the identification of the most vulnerable groups in each disaster hazard scenario. The study adopted a qualitative approach, which involved a triangulation of trend analysis, ranking and scoring, community mapping, wealth ranking, focus group discussions and direct observation among others. District Key Informant interviews were also conducted at the District Health Directorate, District Directorate of Food and Agriculture and the District Offices of the National Disaster Management Organisation. This was done to obtain much detail information regarding these organisations’ capacity to respond to emergency situations including disasters. ﻿The exercise revealed clearly that the Builsa community is not well prepared for any type of disaster given its very low response and recovery capacity. The exercise, however, indicated victims of various disaster hazards and disaster events have always made strenuous efforts to cope with to the immediate effects of climate variability by relying greatly on their social capital and limited available local resources while seeking external support in the long term. The study recommended that resources need to be marshaled at the local, regional and national level to ensure that the activities planned to reduce vulnerabilities in the District are implemented to the letter.